Rapid Synthesis of Acetylated Potato Starch by Microwave Heating with Iodine as Catalyst - Shi1, Yong-Qin; Zeng1, Fan-Kui; Zhou1, Tian-Hong; Liu1, Gang (Asian Journal of Chemistry, 2014)
Potato starches were acetylated with acetic anhydride under different reaction times with the help of microwave heating and iodine as catalyst. Starch acetates with increasing degrees of substitution were obtained using microwave assistance when the reaction time varied from 3 to 25 min. The presense of absorption band in FT-IR at around 1750 cm-1 confirmed the carbonyl group attachment. SEM revealed exo-corrosion and fusion appeared after acetylation. After acetylation, the complex viscosity of starch reduced and G', G'' of native potato starch and acetylated potato starch also showed different trends. The XRD pattern of acetylated potato starch was similar to the native potato starch may due to the low degree of substitution. Starch acetate with degree of substitution 0.01-0.2 is approved by the FDA for food applications, we assumed that the reaction time should be less than 10 min when preparing food grade acetylated potato starch by microwave heating.